2014
DOI: 10.1097/ans.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Barriers to Cognitive Screening in Rural Populations in the United States

Abstract: There is scant research regarding barriers to cognitive screening in rural US populations. This is surprising when there is evidence of the importance of preventative health behaviors such as memory screening that can lead to earlier diagnosis and treatment of Alzheimer's disease and decrease in associated costs. A systematic review of published research revealed modifiable barriers to screening such as lack of knowledge and lack of knowledgeable providers to screen. Recommendations for diminishing barriers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…These percentages are generally comparable to those observed in Chapman et al (2020), who found that approximately 18%-20% of Australian neuropsychologists surveyed used TeleNP for feedback and intervention, while approximately 7% used TeleNP for clinical interview and testing. The general consistency between the Australian survey and the current international survey may reflect the importance of TeleNP service provision to rural or frontier settings (Grosch et al, 2011;Kirk Wiese et al, 2014), and the comparable demand for providing psychological services to rural or frontier communities. Specifically, in the primary countries in these surveys, 28% of Australians (ABS, 2017), 18% of Americans (United States Census Bureau, 2010), and 19% of Canadians (World Bank, 2019) live in areas classified as rural or frontier.…”
Section: Discussionmentioning
confidence: 89%
“…These percentages are generally comparable to those observed in Chapman et al (2020), who found that approximately 18%-20% of Australian neuropsychologists surveyed used TeleNP for feedback and intervention, while approximately 7% used TeleNP for clinical interview and testing. The general consistency between the Australian survey and the current international survey may reflect the importance of TeleNP service provision to rural or frontier settings (Grosch et al, 2011;Kirk Wiese et al, 2014), and the comparable demand for providing psychological services to rural or frontier communities. Specifically, in the primary countries in these surveys, 28% of Australians (ABS, 2017), 18% of Americans (United States Census Bureau, 2010), and 19% of Canadians (World Bank, 2019) live in areas classified as rural or frontier.…”
Section: Discussionmentioning
confidence: 89%
“…Bail et al., 2013), and local practitioners may be less well informed (e.g. Greenaway-Crombie, Snow, Disler, Davis, & Pond, 2012; Weise, Williams, & Tappen, 2014). In many remote areas, populations are ageing, with implications for the availability of family support (as families have moved away) as well as for the local workforce, which may be shrinking (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Five per cent of the health care providers objected to cognitive screening because they believed that patients do not want to be told that they are at risk for a condition with no cure (eg, Alzheimer), and it is important to recognize that some providers do object to routine cognitive screening. However, although the USPSTF determined in 2003 and 2014 that more research was needed, the USPSTF also stated that routine cognitive screening could increase detection of cognitive impairment that would otherwise go unrecognized, with the potential to reduce health care costs and promote patient independence . It is unlikely that one single intervention would be sufficient to help health care providers adhere to guidelines, and a multipronged approach will certainly be necessary.…”
Section: Discussionmentioning
confidence: 99%